Criticism and Artistic Production in the Academic Capitalism: from the Crisis of the Entrepreneurial Model of University to the Educational Turn in the Pedagogies of Art - Mira, Enric; Guirao, Cristina (Arte, Individuo y Sociedad, 2018)
The concept of education has been the subject of social and political artworks since the 60’s and 70’s of the twentieth century, however the artistic approaches of critical nature on universtiy higher education have been punctual and little-known. Starting from the diagnosis of a “University in ruins” in the context of an “academic capitalism”, this paper proposes, first of all, the analysis of a series of artistic productions that, like those of Ian Wallace and Antoni Muntadas, have addressed specifically a critique of the university as an academic and educational institution. Both approaches discuss on the emergence of the bussines university from the crisis of the humboldtian paradigm of university and the failure of the enlightened ideal of emancipation of humanity through scientific progress. Next, it is analyzed how, from a series of contemporary artistic practices, some of them emerged around the so-called “educational turn” of art, a review of artistic pedagogies is carried out, underpinning another possible way for the transformation of the entrepreneurial model of university.
Keywords: University; academia; academic capitalism; entrepreneurial university; educational turn